Burnt, blazed and fermented soybeans: Changes in protein, lipid and phenolic compounds and their consequences in the animal diet (Research, Society and Development, 2021)
Staying on top as one of the world's largest meat producers and exporters requires high-protein, high-energy foods. In this context, Brazil is privileged since, worldwide, it is one of the largest soy producers, whose grain has high commercial and nutritional value, destined for human consumption, oil extraction and animal feed. However, the quality of its by-products is a reflection of the integrity of the grain and of the entire production chain: production, harvest, drying, storage, industrialization and processing. Thus, due to the threat to the quality of animal feed, resulting from the post-harvest stages, and taking into account the legislative standards regarding qualitative classification, changes in protein, lipid and phenolic fractions in fermented soybeans were analyzed, blazed and burnt. Due to the defects, there are lower levels of crude protein, lipids and protein solubility, essences for animal protein formation, and higher values of phenolic compounds. These substances promote complexion with trypsin and chymotrypsin, secreted by the pancreas, preventing their photolytic action, resulting in overload. Consequently, hypertrophy of the organ occurs, in addition to reducing the digestion of the rest of the food present in the intestinal lumen.  Blazed, burned and fermented grains have undesirable characteristics in the animal feed industry, primarily due to their low protein and lipid content. Burnt grains, in particular, not recommended for use in animal nutrition, as result of protein denaturation.